Inovasi Manajemen Elektronifikasi Transaksi Pemerintah Daerah (ETPD): Penguatan Ekosistem Digital untuk Akselerasi Ekonomi Daerah pada Era Digital - Sinulingga, Elsa Natalia (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2025)
Digital transformation in local government financial management has become a strategic agenda to realize transparent, accountable, and efficient governance. Local Government Transaction Electronification (ETPD) as part of the Acceleration and Expansion of Regional Digitalization (P2DD) is a crucial instrument for strengthening the digital economy at the regional level. This research aims to analyze the ETPD management innovation model in strengthening the digital economic ecosystem, identify factors influencing the effectiveness of ETPD implementation, and formulate policy recommendations for optimizing ETPD implementation. Employing a qualitative approach with policy analysis and case study methods, this research collected data through documentation studies, secondary data analysis, in-depth interviews, and observations. The analysis results indicate that an effective ETPD management innovation model consists of four pillars: strengthening regulation and inter-institutional coordination, reinforcing the government digital ecosystem, developing digital infrastructure, and enhancing public digital literacy. ETPD implementation has shown a positive trend with 87.9% of local governments at the Digital level in Semester I of 2024. However, regional disparities persist with Java-Bali recording the highest achievement (66.5%) and Nusampua the lowest (27.1%). The effectiveness of ETPD implementation is influenced by eight factors: leadership and political commitment, regulatory framework, technological infrastructure readiness, human resource capacity, banking partnerships, public digital literacy, inter-institutional coordination, and fiscal incentives. Based on these findings, it is recommended to strengthen inter-institutional partnerships, develop a comprehensive ETPD Roadmap, prioritize digital infrastructure development in frontier regions, enhance digital literacy, establish technical implementation guidelines, develop an integrated digital payment system, and implement an effective monitoring and evaluation system. implications are for Indonesia to immediately implement Law No. 27 of 2022 on Personal Data Protection, establish a centralized data protection authority, and encourage Public-Private Partnerships to improve accountability in personal data protection. Based on these recommendations, it can be concluded that ETPD innovation plays a strategic role in strengthening the digital economic ecosystem of regional governments.